Nodulation and Nitrogen Fixation Behaviour Study in the Myrica Esculenta Buch.- HAM. EX D. Don Trees under Two Different Environmental Conditions - Chaukiyal, S. P.; Khatri, Nirmal; Bhatia, Pallavi; Kannojia, Pooja (Indian Forester, 2014)
Seedlings of Myrica esculenta were grown and assessed for its nodulation and nitrogen fixation behaviour at monthly intervals under two different environmental conditions. No nodule formation was observed in two years old seedlings at two different places i) lower altitude i.e. New Forest (FRI), Dehradun ii) higher altitude i.e. Field Research Station, FRI, Khirsu (Pauri), Uttarakhand, even though an aqueous solution of crushed freshly collected nodules and rhizospheric soil from its naturally grown area was applied under each pot of growing plants. Maximum nodule biomass was recorded in summer followed by rainy and least in winter season. Highest nodule numbers were recorded Â in rainy season followed by summer and minimum in winter. Seasonally higher g-1 fr wt h-1 and pl-1 h-1 nitrogen fixation activity was recorded in rainy season followed by winter and minimum in summer season.